2021
DOI: 10.1590/1806-93042021000100009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with breastfeeding in the first year of life in Cruzeiro do Sul, Acre

Abstract: Objectives: to investigate the factors associated with continued breastfeeding (BF). Methods: All the parturients at a local maternity from July 2015 to June 2016 were invited to participate in a cohort study in Cruzeiro do Sul, Acre. Data on socioeconomic, demographic, obstetric and neonatal of the babies were obtained for the interview. Multiple Poisson regression models with robust variance were used to estimate the prevalence ratio (PR) and 95% confidence intervals (95%CI). Results: among the 1551 mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
0
0
3
Order By: Relevance
“…Com efeito, os estudos têm mostrado que a amamentação promove a redução do peso pós-parto, mas também se evidenciam padrões semelhantes de perda de peso pós-parto entre mulheres lactantes e não lactantes indicando falta de associação entre amamentação e peso materno (Tassinari, 2021;Rodrigues et al, 2021).…”
Section: Amamentação E Obesidadeunclassified
“…Com efeito, os estudos têm mostrado que a amamentação promove a redução do peso pós-parto, mas também se evidenciam padrões semelhantes de perda de peso pós-parto entre mulheres lactantes e não lactantes indicando falta de associação entre amamentação e peso materno (Tassinari, 2021;Rodrigues et al, 2021).…”
Section: Amamentação E Obesidadeunclassified
“…Dentre elas, 69,3% ainda continuavam o aleitamento materno após o bebê completar um ano de idade. As mães que já haviam interrompido a lactação a mantiveram, em média, por cinco meses e referiram o uso de mamadeira e de chupeta como fator associado ao desmame.Inclusive, segundo Alves e colaboradores, é preciso atentar-se quanto à utilização de bicos artificiais, pois esse hábito pode acarretar impactos negativos significativos sobre a amamentação(ALVES et al, 2018;RODRIGUES et al, 2021).Além dos aspectos maternos e socioeconômicos, bem como do nível de conhecimento sobre o manejo da amamentação, fatores dietéticos também interferem no tempo e no tipo de AM. Sob essa ótica, Silva e colaboradores acompanharam 111 mulheres durante a gestação e o primeiro semestre pós-parto e observaram os padrões alimentares delas.…”
unclassified
“…Within the first month, EBF duration was higher among infants born to multiparous mothers and lower among those who were offered a pacifier or had an episode of wheezing (10) . BF frequency in children aged 10 to 15 months was 69.4%, and the factors inversely associated were bottle and pacifier use (11) . Other birth cohort conducted in Rio Branco, the State capital, identified that women's intention to breastfeed for less than six months, alcohol use during pregnancy, lack of breastfeeding in the first hour of life and of EBF at hospital discharge, use of pacifier, and the mother not practicing cross-breastfeeding were factors associated with early weaning before 6 months (12) .…”
Section: Introductionmentioning
confidence: 93%